Efektivitas Senam Kaki dengan Bola Plastik terhadap Sensitivitas Kaki pada Penderita Diabetes Melitus - Ela Susilawati; Faradisa Effendi; Dwi Pantja Wibowo; Feny Kusumadewi; Dian Puspitasari Effendi; Hana Febriyanti (Faletehan Health Journal, 2026)
Peripheral neuropathy is a common complication of diabetes mellitus, characterized by decreased foot sensitivity, which increases the risk of diabetic foot ulcers. Non-pharmacological interventions, such as foot exercises using a plastic ball, are suggested to improve foot sole sensitivity. This study aimed to analyze the effect of foot exercises using a plastic ball on the sensitivity of the right and left feet in patients with diabetes mellitus. This experimental study involved 35 patients with diabetes mellitus at a public health center, selected using purposive sampling. Foot sensitivity was measured before and after the intervention using a 10 g monofilament. Data were analyzed using paired samples t-test to determine significant differences between pretest and posttest at α = 0.05. Foot exercises using a plastic ball effectively improve foot sole sensitivity in patients with diabetes mellitus and can serve as a preventive strategy for peripheral neuropathy and diabetic foot ulcers.